Host relieves lnc‐IRAK3‐3‐sequestered miR‐891b to attenuate apoptosis in Enterovirus 71 infection. (30th May 2019) - Liao, Yu‐Wen; Ho, Bing‐Ching; Chen, Min‐Hsuan; Yu, Sung‐Liang
Abstract: Enterovirus 71 (EV71) is an emerging life‐threatening pathogen particularly in the Asia‐Pacific region. Apoptosis is a major pathogenic feature in EV71 infection. However, which molecular mechanism participating in EV71‐induced apoptosis is not completely understood. Long noncoding RNAs (lncRNAs), a newly discovered class of regulatory RNA molecules, govern a wide range of biological functions through multiple regulatory mechanisms. Whether lncRNAs involved in EV71‐induced apoptosis was investigated in this study. We conducted an apoptosis‐oriented approach by integrating lncRNA and mRNA profilings. lnc‐IRAK3‐3 is down‐regulated in EV71 infection and plays an important role in EV71 infection‐induced apoptosis. Compensation of lnc‐IRAK3‐3 in EV71 infection promoted cell apoptosis wherein GADD45β expression was increased and further triggered caspase3 and PARP cleavage. Using bioinformatics analysis and functional assays, lnc‐IRAK3‐3 could functionally sequester miR‐891b and GADD45β 3′UTR whereas miR‐891b showed the inhibitory activity on GADD45β expression. Taken together, lnc‐IRAK3‐3 has the ability capturing miR‐891b to enforce GADD45β expression and eventually promotes apoptosis. On the contrary, host cells suppress lnc‐IRAK3‐3 to relieve lnc‐IRAK3‐3‐sequestered miR‐891b, restrain GADD45β, and attenuate apoptosis in EV71 infection that prevent host cells from severe damages. We discover a new molecular mechanism by which host cells counteract EV71‐induced apoptosis through the lnc‐IRAK3‐3/miR‐891b/GADD45β axis partially.